2020
DOI: 10.1088/1757-899x/881/1/012069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment on Toughness and Fatigue Behavior Strength of Steel CK45

Abstract: The function of the axle drive shaft is to transfer the engine torque from the gearbox or differential gear to the wheels. It must also endure for all dynamic loads resulted from variations in angle or length during driving from contact the vehicle tire with road. Most problems with the axle drive shaft manifest themselves in the form of knocking noises when driving around tight corners, accelerating, or when the suspension is being compressed and extended where the drive shaft becomes weakened and more subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Results showed that the reinforcing had caused the aluminum alloy's microstructure to become finer. The effect of heat treatment on the fatigue and toughness behavior of CK45 steels was studied by [11], as well as a study of various heat treatments on the microstructure and micro-hardness across the depth of the specimens. The findings showed that compared to other examples, the water quenched steel alloy recorded a greater curve component.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Results showed that the reinforcing had caused the aluminum alloy's microstructure to become finer. The effect of heat treatment on the fatigue and toughness behavior of CK45 steels was studied by [11], as well as a study of various heat treatments on the microstructure and micro-hardness across the depth of the specimens. The findings showed that compared to other examples, the water quenched steel alloy recorded a greater curve component.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…It was demonstrated that materials tempered up to 250 degrees Celsius have improved fatigue characteristics in short-term life zones [14]. In this study, evaluation of the toughness of four different heat treatments was accomplished to get the greatest possible outcome [15]. It was explored that the quenching case's fatigue life was greater in comparison to other situations, and quenching by oil produces the greatest value of toughness.…”
Section: Introductionmentioning
confidence: 99%